Structural analysis of the Wing of UCAV (Unmanned Cargo Aerial Vehicle) using finite element method - Fauzi, AH Fauzi; Pratama, Muhammad Rizky; Silalahi, NH (Trigin Publisher, 2025)
This study analyzes and optimizes the wing structure design of an Unmanned Cargo Aerial Vehicle (UCAV) using the Finite Element Method (FEM). The initial structural assessment shows that the maximum stress of 566.83 MPa occurs at the wing root, resulting in a minimum safety factor of 0.67 which is well below the acceptable threshold of 1.8, as defined by the C.A.S.A Australia Subpart C standard. The maximum displacement amplitude was recorded at 3.81 mm, indicating potential structural failure under operational loads. To improve structural performance, modifications were implemented by increasing the thickness of ribs and spars in critical sections. The redesigned model reduced the maximum stress to 99.97 MPa, raised the minimum safety factor to 1.9, and decreased the maximum displacement amplitude to 0.672 mm. These findings confirm that the modified UCAV wing design achieves compliance with safety standards, enhances structural integrity, and demonstrates improved reliability under operational conditions.